Temperature Measurement in Massive Concrete Structures - Němčic V.; Vítek J.; Lukeš J. (Trans Tech Publications, 2024)
Massive concrete structures are exposed to the risk of high temperatures due to cement hydration. In accordance with requirements for sustainable development, the clinker content in commonly produced cements is reduced and mixed cements are developed and gradually introduced into production. The development of temperatures in massive foundation structures made of concrete containing modern mixed cements is the subject of an experimental program. Its results are evaluated from the point of view of the final properties of the concrete, but also from the point of view of the possibilities of concrete production and implementation technologies. In conclusions, general recommendations are formulated for the design of concrete mixtures for application in massive structures.
Keywords: Concrete; Heat of Hydration; Mixed Cement; Temperature